Preparation method of high-density C / SiC ceramic composite material and product thereof
By optimizing the PIP process, using Pickering emulsion and irregularly shaped carbon fiber braids, and combining heat treatment, the problems of high density and densification in the preparation of C/SiC composite materials were solved, and the efficient preparation of high-performance irregularly shaped C/SiC ceramic composite materials was achieved.
Patent Information
- Application Number
- CN202510977991.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-16
- Publication Date
- 2025-11-11
AI Technical Summary
Existing technologies for preparing C/SiC composite materials, especially for irregularly shaped structural parts, suffer from problems such as long preparation cycles and difficulty in achieving high density and compaction. The traditional PIP method requires multiple rounds of cyclic impregnation and is difficult to achieve a high density of 2.0 g/cm³ or higher.
Pickering emulsion was used instead of precursor solution for multiple impregnation and pyrolysis treatments. Combined with polycarbosilane solution and heat treatment, the PIP process was optimized. A special-shaped carbon fiber braid was used, and the material density was improved through machining and supplementary heat treatment.
It achieves high density (≥2g/cm³) of irregularly shaped C/SiC ceramic composite materials, shortens the preparation cycle, improves the tensile strength and impact toughness of the material, is suitable for complex components and customized products, and reduces production costs and time.
Smart Images

Figure FT_1 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of C / SiC ceramic composite material molding technology, specifically to a method for preparing high-density C / SiC ceramic composite materials and its products. Background Technology
[0002] C / SiC composite materials possess high strength, modulus, ablation resistance, and excellent high-temperature mechanical properties, making them suitable for cutting-edge fields such as aerospace. C / SiC composite materials can effectively withstand the harsh environment of engines, exhibiting long-term stable ablation resistance and oxidation resistance. With the continuous improvement of aircraft performance and the increasing demands for reliability in complex environments, C / SiC composite materials not only need to possess higher density, strength, and thermal stability, but also often need to be fabricated into complex shapes or irregular structures, such as rudder components or leading-edge structures, to meet the requirements of functional integration and structural optimization. Especially with the continuous research on hypersonic equipment, various irregularly shaped structural products are increasingly being used in engine structures.
[0003] Currently, the main methods for preparing C / SiC composites include polymer infiltration and pyrolysis (PIP) and melt infiltration (MI). Among these, the PIP method offers advantages such as a more flexible process flow and applicability to complex-shaped parts, making it valuable for the fabrication of irregularly shaped components. This method involves impregnating a liquid precursor, such as polycarbosilane (PCS), into a carbon fiber preform, followed by high-temperature pyrolysis to form a silicon carbide ceramic matrix. This process is repeated in cycles to increase density.
[0004] However, the traditional PIP process has the following key problems in practical applications: Multiple impregnation cycles are required: usually more than 16 to 17 impregnation-pyrolysis cycles are required to achieve a high density (>1.9 g / cm³), resulting in a long preparation cycle and high energy consumption.
[0005] High density is difficult to achieve: For high-density C / SiC composite materials with a density requirement of 2.0 g / cm³ and above, the traditional PIP method is significantly more difficult to prepare, especially in irregularly shaped parts, where densification is more difficult due to the complex internal structure and the difficulty in fully penetrating and venting the pores.
[0006] Therefore, there is an urgent need to provide a method for preparing C / SiC ceramic composite materials with high density suitable for irregularly shaped components, in order to meet the engineering application requirements of next-generation high-performance thermal structural materials. Based on the above problems, this invention proposes a novel preparation method with optimized process, which can effectively improve the density of irregularly shaped C / SiC composite materials, shorten the preparation cycle, and has good prospects for industrial application. Summary of the Invention
[0007] To overcome the shortcomings of the above-mentioned technologies, the purpose of this invention is to provide a method for preparing high-density C / SiC ceramic composite materials and the product thereof, which can effectively improve the bulk density of C / SiC ceramic composite materials.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a high-density C / SiC ceramic composite material, characterized by the following steps: 1) Preform preparation: The carbon fiber braid is degummed and pyrolytic carbon is deposited to obtain a preform with pyrolytic carbon deposited on it; 2) A precursor solution was prepared using polycarbosilane as a precursor. The preform was subjected to multiple impregnation and pyrolysis treatments using the PIP process to obtain a density ≥1.75 g / cm³. 3 The blank; 3) A Pickering emulsion was prepared using silicon carbide as a raw material. This Pickering emulsion was then used to replace the precursor solution in multiple impregnation and pyrolysis treatments of the billet to obtain a density ≥2.0 g / cm³. 3 The billet is then subjected to a final impregnation pyrolysis treatment using the precursor solution. 4) The blank after impregnation and pyrolysis is machined and then heat-treated to obtain C / SiC ceramic composite material products.
[0009] As a preferred embodiment, the carbon fiber braid has an irregular structure; the shape of the irregular structure includes one or more combinations of cylindrical, conical, pyramidal, prismal, trapezoidal, spherical, square, cylindrical, arc-shaped, and irregular triangle.
[0010] As a preferred embodiment, in step 1), the degumming process includes: placing the carbon fiber braid into a high-temperature furnace, starting the CNC panel to set the heating program, and performing a three-stage heating process; the first stage heating: heating from 400 to 800°C for 400-800 minutes to 800-1000°C, and holding for 100±30 minutes; the second stage heating: heating from 400 to 600 minutes to 1600-1800°C, and holding for 100±30 minutes; the third stage heating: heating from 100 to 200 minutes to 1900-2500°C, and holding for 240±30 minutes; during the first stage heating process, argon gas is introduced during the holding period, the flow rate of the argon gas is 1-3 L / min, and the pressure inside the furnace is maintained at 4-8 KPa until the three-stage heating process is completed; after the heating is completed, the furnace is cooled to below 50°C, and the product is removed.
[0011] As a preferred embodiment, in step 1), the pyrolysis carbon deposition process includes: transferring the degummed carbon fiber braid into a vapor deposition furnace, heating to 700-1000℃ for 720-1440 min, and holding at that temperature for 4320-5760 min; during the holding period, introducing a mixed gas of methane and argon with a volume ratio of 3.5-4.5:1 at a flow rate of 1-3 L / min, while simultaneously evacuating to a negative pressure inside the furnace and maintaining the negative pressure inside the furnace at 500-900 kPa until the heating is completed; after the heating is completed, cooling the product to below 50℃ with the furnace and removing the product; the heating program is controlled by an automatic control valve.
[0012] As a preferred embodiment, in step 2), the precursor solution comprises solid polycarbosilane and xylene in a mass ratio of 1:0.7~1.5.
[0013] Furthermore, the method for preparing the precursor solution includes: adding solid polycarbosilane and xylene in a mass ratio of 1:0.7~1.5 into a special impregnation tool, starting mechanical stirring at a stirring speed of 150~200 rpm until a clear solution is completely formed.
[0014] As a preferred embodiment, in steps 2) and 3), the impregnation pyrolysis process includes the following steps: Impregnation: The preform or blank is placed into an impregnation fixture containing a precursor solution, or the blank is placed into an impregnation fixture containing a Pickering emulsion, requiring all surfaces to be submerged, and the impregnation time is 12~36h; Curing: Take out the preform or blank after soaking, shape it with a shaping fixture, and cure it at a constant temperature of 40~60℃ for 12~36h to obtain a blank with the shaping fixture. Pyrolysis: The billet carrying the shaping fixture is transferred to the pyrolysis furnace. First, the furnace is evacuated to below 10 Pa, and nitrogen is introduced to replace the air in the furnace three times. Then, the furnace is evacuated again to 9~11 Pa. Next, the heating program is set on the CNC panel and two-stage holding is performed. The first stage: heating to 800~1000℃ in 400~800 min and holding for 100±20 min. The second stage: heating to 1000~1500℃ in 400~600 min and holding for 150±10 min. After the holding is completed, the furnace is cooled to below 50℃, the vacuum is released, the billet is taken out and the shaping fixture is removed.
[0015] Furthermore, the shaping fixture is a graphite fixture.
[0016] As a preferred embodiment, in step 3), the Pickering emulsion comprises silicon carbide, xylene, and emulsifier in a mass ratio of 3:1.0~1.8:0.05.
[0017] Furthermore, the emulsifier is silicon dioxide or a modified silicon dioxide emulsifier; the silicon carbide is waste silicon carbide powder generated during the pyrolysis process.
[0018] As a preferred embodiment, in step 4), the temperature of the heat treatment is 1000±50℃.
[0019] Furthermore, the heat treatment process includes: transferring the machined billet to a pyrolysis furnace, firstly evacuating the furnace to below 10 Pa, then filling the furnace with nitrogen to replace the air three times, and then evacuating it again to 9~11 Pa; starting the CNC panel to set the heating program, heating to 1000±50℃ in 400~800 min, and holding at that temperature for 100±20 min; after the holding period, cooling the billet to below 50℃ with the furnace, removing the vacuum, and taking out the product.
[0020] This invention also provides a high-density C / SiC ceramic composite material product, characterized in that it is obtained by the above-described preparation method; the high-density C / SiC ceramic composite material product has a tensile strength ≥330 MPa and an impact toughness ≥40 KJ / (m²). 2 (), bulk density ≥2g / cm³ 3 .
[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention discloses a method for preparing high-density C / SiC ceramic composite materials, which effectively improves the bulk density of the final product sample, resulting in a product with high bulk density and good mechanical properties. This invention utilizes carbon fiber braids with irregular structures as raw materials, improving the overall three-dimensional strength and fracture toughness of the composite material. It is suitable for processing complex components or customized products, ensuring minimal deviation and high product quality for irregularly shaped products. The process flow of this invention can completely eliminate manual labor, automating production lines, reducing manual input, liberating productivity, improving work efficiency, and minimizing process risk. While traditional processes require a production cycle of at least three months, this invention can complete product production in two months. The C / SiC ceramic composite material prepared by this method exhibits a tensile strength ≥336 MPa and an impact toughness ≥40 KJ / (m²). 2 (), bulk density ≥2g / cm³ 3 It meets the performance requirements of high-density, high-mechanical-performance C / SiC ceramic composites, and is especially suitable for the preparation of irregularly shaped C / SiC ceramic composites. Attached Figure Description
[0022] Figure 1 This is a schematic diagram of the structure of the carbon fiber braid in a specific embodiment of the present invention. Detailed Implementation
[0023] To better explain the present invention, the main contents of the present invention are further illustrated below with reference to specific embodiments, but the contents of the present invention are not limited to the following embodiments.
[0024] The domestically produced irregular-shaped carbon fiber braided fabric used in the examples and comparative examples employs continuous long carbon fiber soft-layup, with the layup direction (0 / 90°) and the Z-direction stitched with bidirectional carbon fiber penetration. The bulk density is 0.75~0.85 g / cm³. 3 Among them, such as Figure 1 As shown, the domestically produced irregular carbon fiber braid is a thick fabric woven from braids, with an irregular structure, which is a triangle with two curved sides.
[0025] Example 1 A method for preparing a high-density C / SiC ceramic composite material includes the following steps: 1) Preform preparation: The carbon fiber braid is degummed and subjected to pyrolytic carbon deposition to obtain a preform with deposited pyrolytic carbon; the carbon fiber braid is a domestically produced irregular-shaped carbon fiber braid; the specific operation is as follows: The carbon fiber braid was placed into a high-temperature furnace, and the heating program was set on the CNC panel for a three-stage heating process: Stage 1: Heating to 1000℃ in 800 minutes and holding for 80 minutes; Stage 2: Heating to 1800℃ in 600 minutes and holding for 80 minutes; Stage 3: Heating to 2400℃ in 200 minutes and holding for 200 minutes. During the first stage heating process, argon gas was introduced at a flow rate of 3 L / min, maintaining a furnace pressure of 8 kPa until the end of the three-stage heating process. After the heating was completed, the product was cooled to below 50℃ in the furnace and then removed. The heating program was controlled by an automatic control valve. The cooled product is transferred into a vapor deposition furnace, and the heating program is set on the CNC panel. The temperature is increased to 1000℃ in 1440 minutes and held for 5700 minutes. During the holding period, a mixture of methane and argon with a volume ratio of 4:1 is introduced at a flow rate of 3L / min. At the same time, a vacuum is drawn to create a negative pressure inside the furnace, which is maintained at 900KPa until the heating ends. After the heating ends, the product is cooled to below 50℃ in the furnace to obtain the preform. The heating program is controlled by an automatic control valve.
[0026] 2) Polycarbosilane precursor solution / product PIP impregnation pyrolysis method: A precursor solution is prepared using polycarbosilane as a precursor. The preform is subjected to multiple impregnation pyrolysis treatments using the PIP process to obtain a product with a density of 1.75 g / cm³. 3 The specific procedures for impregnation and pyrolysis treatment of the billet are as follows: Impregnation: Add solid polycarbosilane and xylene to the impregnation fixture at a mass ratio of 1:1.5, start mechanical stirring at a stirring speed of 200 rpm until a clear solution is completely formed; put the preform into the impregnation fixture, requiring all surfaces to be submerged, and soak for 36 hours; Curing: After soaking, the material is pressurized and shaped using graphite tooling. The pyrolysis process also involves using graphite tooling to maintain the required shape. The material is then transferred to a 50°C constant temperature chamber for curing, which takes 36 hours. Pyrolysis: After solidification, the billet carrying the graphite shaping fixture is transferred to the pyrolysis furnace. First, the furnace is evacuated to below 10 Pa, then nitrogen is introduced to replace the air in the furnace three times, and the furnace is evacuated to 10 Pa again. The heating program is set on the CNC panel and a two-stage heating process is carried out. The first stage: heating to 1000℃ in 800 minutes and holding for 80 minutes; the second stage: heating to 1500℃ in 600 minutes and holding for 140 minutes. After the holding period, the billet is cooled to below 50℃ in the furnace, the vacuum is released, the billet is taken out, and the shaping fixture is removed. The process continues until the billet density reaches 1.75 g / cm³. 3 .
[0027] 3) Silicon carbide mixed solution / supplementary impregnation pyrolysis: Using the waste silicon carbide powder generated during the polycarbosilane pyrolysis process in step 2), a Pickering emulsion was prepared. This Pickering emulsion was used to replace the precursor solution for multiple impregnation pyrolysis treatments of the billet to obtain a density ≥2.0 g / cm³. 3 The billet is then subjected to a final impregnation pyrolysis treatment using a precursor solution; the specific operation is as follows: Waste silicon carbide powder from the previous pyrolysis furnace was collected and mixed with xylene and silica emulsifier in a special impregnation tool at a mass ratio of 3:1.8:0.05 to prepare Pickering emulsion; The blank is fully immersed in the Pickering emulsion by applying pressure using a shaping fixture; then, curing and pyrolysis are carried out according to step 2). Repeat the Pickering emulsion impregnation, curing, and pyrolysis process until the billet density reaches 2.0 g / cm³. 3 And above; finally, add a round of impregnation, solidification and pyrolysis of the precursor solution in step 2).
[0028] The total number of impregnation and pyrolysis cycles in steps 2) and 3) is 12.
[0029] 4) Machining / Supplementary heat treatment of rough blank surface: Machining the blank after impregnation and pyrolysis, followed by heat treatment, to obtain C / SiC ceramic composite material products.
[0030] The blank is shaped and machined using a CNC milling machine. Because stress is stored during the machining process, this can lead to a certain reduction in the performance of the finished product and pose a quality risk. Therefore, a 1000℃ heat treatment is performed after the shaped and machined surface is completed. The specific operation is as follows: After machining, the billet is transferred to a pyrolysis furnace. First, the furnace is evacuated to below 10 Pa, then nitrogen is introduced to replace the air in the furnace three times, followed by another evacuation to 10 Pa. The temperature rise program is then set on the CNC panel, reaching 1000℃ in 800 minutes and holding for 80 minutes. After holding, the furnace is cooled to below 50℃, the vacuum is released, and the product is removed, yielding the C / SiC ceramic composite material.
[0031] Example 2 A method for preparing a high-density C / SiC ceramic composite material includes the following steps: 1) Preform preparation: The carbon fiber braid is degummed and subjected to pyrolytic carbon deposition to obtain a preform with deposited pyrolytic carbon; the carbon fiber braid is a non-standard domestically produced carbon fiber braid; the specific operation is as follows: The carbon fiber braid was placed into a high-temperature furnace, and the heating program was set on the CNC panel for a three-stage heating process: Stage 1: Heating to 900℃ in 600 minutes, holding for 100 minutes; Stage 2: Heating to 1700℃ in 500 minutes, holding for 100 minutes; Stage 3: Heating to 2200℃ in 150 minutes, holding for 240 minutes. During the first stage heating, argon gas was introduced at a flow rate of 2L / min, maintaining a furnace pressure of 6KPa until the end of the three-stage heating process. After heating, the product was cooled to below 50℃ in the furnace and then removed. The heating program was controlled by an automatic control valve. The cooled product is transferred into a vapor deposition furnace, and the heating program is set on the CNC panel. The temperature is increased to 850℃ in 1150 minutes and held for 5000 minutes. During the holding period, a mixture of methane and argon with a volume ratio of 4:1 is introduced at a flow rate of 2L / min. At the same time, a vacuum is drawn to create a negative pressure inside the furnace, which is maintained at 700KPa until the heating ends. After the heating ends, the product is cooled to below 50℃ in the furnace to obtain the preform. The heating program is controlled by an automatic control valve.
[0032] 2) Polycarbosilane precursor solution / product PIP impregnation pyrolysis method: A precursor solution is prepared using polycarbosilane as a precursor. The preform is subjected to multiple impregnation pyrolysis treatments using the PIP process to obtain a density of 1.8 g / cm³. 3 The specific procedures for impregnation and pyrolysis treatment of the billet are as follows: Impregnation: Add solid polycarbosilane and xylene to the impregnation fixture at a mass ratio of 1:1.1, start mechanical stirring at a stirring speed of 175 rpm until a clear solution is completely formed; put the preform into the impregnation fixture, requiring all surfaces to be submerged, and soak for 24 hours; Curing: After soaking, the material is pressurized and shaped using graphite tooling. The pyrolysis process also involves using graphite tooling to maintain the required shape. The soaked billet is then removed and transferred to a 50°C constant temperature chamber for curing, which takes 24 hours. Pyrolysis: After solidification, the billet carrying the graphite shaping fixture is transferred to the pyrolysis furnace. First, the furnace is evacuated to below 10 Pa, and nitrogen is introduced to replace the air in the furnace three times. Then, the furnace is evacuated to 10 Pa again. The heating program is set on the CNC panel and a two-stage heating process is carried out. The first stage is heating to 900℃ in 600 minutes and holding for 100 minutes. The second stage is heating to 1300℃ in 500 minutes and holding for 150 minutes. After the holding period, the billet is cooled to below 50℃ in the furnace, the vacuum is released, the billet is taken out, and the shaping fixture is removed.
[0033] The process continues until the billet density reaches 1.8 g / cm³. 3 .
[0034] 3) Silicon carbide mixed solution / supplementary impregnation pyrolysis: Using the waste silicon carbide powder generated during the polycarbosilane pyrolysis process in step 2), a Pickering emulsion was prepared. This Pickering emulsion was used to replace the precursor solution for multiple impregnation pyrolysis treatments of the billet to obtain a density ≥2.0 g / cm³. 3 The billet is then subjected to a final impregnation pyrolysis treatment using a precursor solution; the specific operation is as follows: Waste silicon carbide powder from the previous pyrolysis furnace was collected and mixed with xylene and silica emulsifier in a special impregnation tool at a mass ratio of 3:1.4:0.05 to prepare Pickering emulsion; The blank is fully immersed in the Pickering emulsion by applying pressure using a shaping fixture; then, curing and pyrolysis are carried out according to step 2). Repeat the Pickering emulsion impregnation, curing, and pyrolysis process until the billet density reaches 2.0 g / cm³. 3 And above; finally, add a round of impregnation, solidification and pyrolysis of the precursor solution in step 2).
[0035] The total number of impregnation and pyrolysis cycles in steps 2) and 3) is 12.
[0036] 4) Machining / Supplementary heat treatment of rough billet surface: The billet after impregnation and pyrolysis is machined and then heat-treated to obtain C / SiC ceramic composite material products. The specific operation is as follows: The blank is machined by CNC milling machine. Since stress is stored during the machining process, it will reduce the performance of the finished product and cause quality risks. Therefore, after the machining is completed, a heat treatment of 1000℃ is added. After machining, the billet is transferred to a pyrolysis furnace. First, the furnace is evacuated to below 10 Pa, then nitrogen is introduced to replace the air in the furnace three times, and the furnace is evacuated again to 10 Pa. The heating program is then set on the CNC panel, heating to 950℃ in 600 minutes and holding at that temperature for 120 minutes. After the holding period, the furnace is cooled to below 50℃, the vacuum is released, and the product is removed, thus obtaining the C / SiC ceramic composite material product.
[0037] Example 3 A method for preparing a high-density C / SiC ceramic composite material includes the following steps: 1) Preform preparation: The carbon fiber braid is degummed and subjected to pyrolytic carbon deposition to obtain a preform with deposited pyrolytic carbon; the carbon fiber braid is a domestically produced irregular-shaped carbon fiber braid; the specific operation is as follows: The carbon fiber braid was placed into a high-temperature furnace, and the heating program was set on the CNC panel for a three-stage heating process: Stage 1: Heating to 800℃ in 400 minutes, holding for 120 minutes; Stage 2: Heating to 1600℃ in 400 minutes, holding for 130 minutes; Stage 3: Heating to 1900℃ in 110 minutes, holding for 270 minutes. During the first stage heating, argon gas was introduced at a flow rate of 1.2 L / min, maintaining a furnace pressure of 4 kPa until the end of the three-stage heating process. After heating, the product was cooled to below 50℃ in the furnace and then removed. The heating program was controlled by an automatic control valve. The cooled product is transferred into a vapor deposition furnace, and the heating program is set on the CNC panel. The temperature is increased to 700℃ in 720 minutes and held for 4400 minutes. During the holding period, a mixture of methane and argon with a volume ratio of 4:1 is introduced at a flow rate of 1L / min. At the same time, a vacuum is drawn to create a negative pressure inside the furnace, which is maintained at 500KPa until the heating ends. After the heating ends, the product is cooled to below 50℃ in the furnace to obtain the preform. The heating program is controlled by an automatic control valve.
[0038] 2) Polycarbosilane precursor solution / product PIP impregnation pyrolysis method: A precursor solution is prepared using polycarbosilane as a precursor. The preform is subjected to multiple impregnation pyrolysis treatments using the PIP process to obtain a product with a density of 1.78 g / cm³. 3 The specific procedures for impregnation and pyrolysis treatment of the billet are as follows: Impregnation: Add solid polycarbosilane and xylene to the impregnation fixture at a mass ratio of 1:0.7, start mechanical stirring at a stirring speed of 150 rpm until a clear solution is completely formed; put the preform into the impregnation fixture, requiring all surfaces to be submerged, and soak for 12 hours; Curing: After soaking, the material is pressed and shaped using graphite tooling, and the pyrolysis process also carries the graphite tooling to maintain the required shape; then it is transferred to a 50℃ constant temperature chamber for curing, and the curing time is 12 hours. Pyrolysis: After solidification, the billet carrying the graphite shaping fixture is transferred to the pyrolysis furnace. First, the furnace is evacuated to below 10 Pa, then nitrogen is introduced to replace the air in the furnace three times, and the furnace is evacuated to 10 Pa again. The heating program is set on the CNC panel and a two-stage heating process is carried out. The first stage: heating to 800℃ in 400 minutes and holding for 120 minutes; the second stage: heating to 1000℃ in 400 minutes and holding for 160 minutes. After the holding period, the billet is cooled to below 50℃ in the furnace, the vacuum is released, the billet is taken out, and the shaping fixture is removed. The process continues until the billet density reaches 1.78 g / cm³. 3 .
[0039] 3) Silicon carbide mixed solution / supplementary impregnation pyrolysis: Using the waste silicon carbide powder generated during the polycarbosilane pyrolysis process in step 2), a Pickering emulsion was prepared. This Pickering emulsion was used to replace the precursor solution for multiple impregnation pyrolysis treatments of the billet to obtain a density ≥2.0 g / cm³. 3 The billet is then subjected to a final impregnation pyrolysis treatment using a precursor solution; the specific operation is as follows: Waste silicon carbide powder from the previous pyrolysis furnace was collected and mixed with xylene and silica emulsifier in a special impregnation tool at a mass ratio of 3:1.0:0.05 to prepare Pickering emulsion; The blank is fully immersed in the Pickering emulsion by applying pressure using a shaping fixture; then, curing and pyrolysis are carried out according to step 2). Repeat the Pickering emulsion impregnation, curing, and pyrolysis process until the billet density reaches 2.0 g / cm³. 3 And above; finally, add a round of impregnation, solidification and pyrolysis of the precursor solution in step 2).
[0040] The total number of impregnation and pyrolysis cycles in steps 2) and 3) is 13.
[0041] 4) Machining / Supplementary heat treatment of rough blank surface: Machining the blank after impregnation and pyrolysis, followed by heat treatment, to obtain C / SiC ceramic composite material products.
[0042] The blank is shaped and machined using a CNC milling machine. Because stress is stored during the machining process, this can lead to a certain reduction in the performance of the finished product and pose a quality risk. Therefore, a 1000℃ heat treatment is performed after the shaped and machined surface is completed. The specific operation is as follows: After machining, the billet is transferred to a pyrolysis furnace. First, the furnace is evacuated to below 10 Pa, then nitrogen is introduced to replace the air in the furnace three times, followed by another evacuation. The heating program is then set on the CNC panel, heating to 950℃ in 400 minutes and holding for 100 minutes. After holding, the furnace is cooled to below 50℃, the vacuum is released, and the product is removed, thus obtaining the C / SiC ceramic composite material.
[0043] Comparative Example 1 A method for preparing a high-density C / SiC ceramic composite material includes the following steps: 1) Preform preparation: The carbon fiber braid is degummed and subjected to pyrolytic carbon deposition to obtain a preform with deposited pyrolytic carbon; the carbon fiber braid is a domestically produced irregular-shaped carbon fiber braid; the specific operation is as follows: The domestically produced carbon fiber braid was placed in a high-temperature furnace, and the heating program was set on the CNC panel for a three-stage heating process: First stage: heating to 800℃ in 400 minutes, holding for 120 minutes; Second stage: heating to 1600℃ in 400 minutes, holding for 130 minutes; Third stage: heating to 1900℃ in 110 minutes, holding for 270 minutes. During the first stage heating, argon gas was introduced at a flow rate of 1.2 L / min, maintaining a furnace pressure of 4 kPa until the end of the three-stage heating process. After the heating was completed, the product was cooled to below 50℃ in the furnace and then removed. The heating program was controlled by an automatic control valve. The cooled product is transferred into a vapor deposition furnace, and the heating program is set on the CNC panel. The temperature is increased to 700℃ in 720 minutes and held for 4400 minutes. During the holding period, a mixture of methane and argon with a volume ratio of 4:1 is introduced at a flow rate of 1L / min. At the same time, a vacuum is drawn to create a negative pressure inside the furnace, which is maintained at 500KPa until the heating ends. After the heating ends, the product is cooled to below 50℃ in the furnace to obtain the preform. The heating program is controlled by an automatic control valve.
[0044] 2) Polycarbosilane precursor solution / product PIP impregnation pyrolysis method: A precursor solution is prepared using polycarbosilane as a precursor. The preform is subjected to multiple impregnation pyrolysis treatments using the PIP process to obtain a product with a density of 1.55 g / cm³. 3 The specific procedures for impregnation and pyrolysis treatment of the billet are as follows: Impregnation: Add solid polycarbosilane and xylene to the impregnation fixture at a mass ratio of 1:0.7, start mechanical stirring at a stirring speed of 150 rpm until a clear solution is completely formed; put the preform into the impregnation fixture, requiring all surfaces to be submerged, and soak for 12 hours; Curing: After soaking, the material is pressed and shaped using graphite tooling, and the pyrolysis process also carries the graphite tooling to maintain the required shape; then it is transferred to a 50℃ constant temperature chamber for curing, and the curing time is 12 hours. Pyrolysis: After solidification, the billet carrying the graphite shaping fixture is transferred to the pyrolysis furnace. First, the furnace is evacuated to below 10 Pa, then nitrogen is introduced to replace the air in the furnace three times, and the furnace is evacuated to 10 Pa again. The heating program is set on the CNC panel and a two-stage heating process is carried out. The first stage: heating to 800℃ in 400 minutes and holding for 120 minutes; the second stage: heating to 1000℃ in 400 minutes and holding for 160 minutes. After the holding period, the billet is cooled to below 50℃ in the furnace, the vacuum is released, the billet is taken out, and the shaping fixture is removed. Circulate until the billet density reaches 1.55 g / cm³. 3 .
[0045] 3) Silicon carbide mixed solution / supplementary impregnation pyrolysis: Using the waste silicon carbide powder generated during the polycarbosilane pyrolysis process in step 2), a Pickering emulsion was prepared. This Pickering emulsion was used to replace the precursor solution for multiple impregnation pyrolysis treatments of the billet to obtain a density ≥2.0 g / cm³. 3 The billet is then subjected to a final impregnation pyrolysis treatment using a precursor solution; the specific operation is as follows: Waste silicon carbide powder from the previous pyrolysis furnace was collected and mixed with xylene and silica emulsifier in a special impregnation tool at a mass ratio of 3:1.0:0.05 to prepare Pickering emulsion; The blank is bent and immersed in the Pickering emulsion by applying pressure with a shaping fixture; then it is cured and pyrolyzed according to step 2). Repeat the Pickering emulsion impregnation, curing, and pyrolysis process until the billet density reaches 2.0 g / cm³. 3 And above; finally, a round of polycarbosilane precursor impregnation pyrolysis is added.
[0046] The total number of impregnation and pyrolysis cycles in steps 2) and 3) is 13.
[0047] 4) Machining / Supplementary heat treatment of rough blank surface: Machining the blank after impregnation and pyrolysis, followed by heat treatment, to obtain C / SiC ceramic composite material products.
[0048] The blank is shaped and machined using a CNC milling machine. Because stress is stored during the machining process, this can lead to a certain reduction in the performance of the finished product and pose a quality risk. Therefore, an additional heat treatment at 800℃ is performed after the shaped and machined surface is completed. The specific operation is as follows: After machining, the billet is transferred to a pyrolysis furnace. First, the furnace is evacuated to below 10 Pa, then nitrogen is introduced to replace the air in the furnace three times, followed by another evacuation. The temperature rise program is then set on the CNC panel, reaching 800℃ in 400 minutes and holding for 100 minutes. After the holding period, the furnace is cooled to below 50℃, the vacuum is released, and the product is removed, thus obtaining the C / SiC ceramic composite material.
[0049] Comparative Example 2 A method for preparing a high-density C / SiC ceramic composite material includes the following steps: 1) Preform preparation: The carbon fiber braid is degummed and subjected to pyrolytic carbon deposition to obtain a preform with deposited pyrolytic carbon; the carbon fiber braid is a domestically produced irregular-shaped carbon fiber braid; the specific operation is as follows: The carbon fiber braid was placed into a high-temperature furnace, and the heating program was set on the CNC panel for a three-stage heating process: Stage 1: Heating to 900℃ in 600 minutes, holding for 100 minutes; Stage 2: Heating to 1700℃ in 500 minutes, holding for 100 minutes; Stage 3: Heating to 2200℃ in 150 minutes, holding for 240 minutes. During the first stage heating, argon gas was introduced at a flow rate of 2L / min, maintaining a furnace pressure of 6KPa until the end of the three-stage heating process. After heating, the product was cooled to below 50℃ in the furnace and then removed. The heating program was controlled by an automatic control valve. The cooled product is transferred into a vapor deposition furnace, and the heating program is set on the CNC panel. The temperature is increased to 850℃ in 1150 minutes and held for 5000 minutes. During the holding period, a mixture of methane and argon with a volume ratio of 4:1 is introduced at a flow rate of 2L / min. At the same time, a vacuum is drawn to create a negative pressure inside the furnace, which is maintained at 700KPa until the heating ends. After the heating ends, the product is cooled to below 50℃ in the furnace to obtain the preform. The heating program is controlled by an automatic control valve.
[0050] 2) Polycarbosilane precursor solution / product PIP impregnation and pyrolysis method: A precursor solution is prepared using polycarbosilane as a precursor. The preform is subjected to multiple impregnation and pyrolysis treatments using the PIP process to obtain a density ≥1.75 g / cm³. 3 The specific procedures for impregnation and pyrolysis treatment of the billet are as follows: Solid polycarbosilane and xylene are added to the impregnation fixture at a mass ratio of 1:1.1. Mechanical stirring is started at a stirring speed of 175 rpm until a clear solution is completely formed. The pre-treated preform is then placed into the impregnation fixture, ensuring that all surfaces are submerged. The soaking time is 24 hours. Curing: After soaking, the material is pressed and shaped using graphite tooling, and the pyrolysis process also carries the graphite tooling to maintain the required shape; then it is transferred to a 50℃ constant temperature chamber for curing, and the curing time is 24 hours. Pyrolysis: After solidification, the material is transferred to a pyrolysis furnace. First, the furnace is evacuated to below 10 Pa, and nitrogen is introduced to replace the air in the furnace three times. Then, the furnace is evacuated to 10 Pa again. The heating program is set on the CNC panel and a two-stage heating process is performed. The first stage is heating to 900℃ in 600 minutes and holding for 100 minutes. The second stage is heating to 1300℃ in 500 minutes and holding for 150 minutes. After the holding period, the material is cooled to below 50℃ in the furnace, the vacuum is released, the billet is removed, and the shaping fixtures are taken out.
[0051] Circulate until the billet density is ≥1.85 g / cm³ 3 .
[0052] In step 2), the total number of impregnation and pyrolysis cycles is 17. Subsequent impregnation and pyrolysis cannot further increase the density.
[0053] 3) Machining of rough blank surface The blank is machined using a CNC milling machine to achieve the shape required by the design drawings.
[0054] The C / SiC ceramic composite materials prepared in the above examples and comparative examples were tested respectively. The tensile strength of the samples was tested according to the national standard GB / T1447-2005, and the impact toughness of the samples was tested according to the national standard GB / T1043.1-2008. The results are shown in Table 1.
[0055] Table 1: Product Performance Test Results Table 1 shows that in Comparative Example 1, the product's impact toughness and tensile strength were insufficient due to unsuitable intermediate density and insufficient heat treatment temperature, making it prone to cracking and failing to meet product requirements. In Comparative Example 2, the irregularly shaped C / SiC ceramic composite material was prepared using existing technology, and after 17 impregnation and pyrolysis cycles, the bulk density reached 1.85 g / cm³. 3 The above results showed that subsequent impregnation and pyrolysis attempts failed to achieve a bulk density of 2 g / cm³. 3 Furthermore, its impact toughness and tensile strength are also relatively low, failing to meet the performance requirements of the product.
[0056] In Examples 1-3, using the method of the present invention, a bulk density ≥2g / cm³ can be achieved with only 12-13 impregnation-pyrolysis cycles. 3 Compared with the conventional method involving 17 impregnation and pyrolysis cycles, this method shortens the preparation cycle. The irregularly shaped C / SiC ceramic composite materials prepared using the method of this invention in Examples 1-3 exhibit tensile strength ≥336 MPa and impact toughness ≥40 KJ / (m²). 2 All have a bulk density ≥2g / cm³ 3 To meet the performance requirements of the product.
[0057] Therefore, this invention can use carbon fiber braids with irregular structures as raw materials to obtain high-density C / SiC ceramic composite materials with irregular structures, ensuring small deviations and high product quality, suitable for molding and processing complex components or customized products. This invention improves the utilization rate of raw materials and saves costs by collecting and using waste silicon carbide powder from previous pyrolysis to prepare Pickering emulsions. Furthermore, the silicon carbide powder effectively fills the micropores, achieving densification, and the resulting products all have a bulk density ≥2 g / cm³. 3This invention eliminates the performance degradation caused by machining through supplementary heat treatment, and solves the problem of internal stress in C / SiC composite products after machining. It causes the silicon carbide matrix molecules within the billet to move, thereby eliminating internal stress and improving the product's strength and toughness. The tensile strength of the product is ≥336 MPa, and the impact toughness is ≥40 KJ / (m²). 2 This invention overcomes the problems of low densification efficiency and excessive porosity in traditional PIP processes by combining the PIP process with a method of repeated alternating impregnation and pyrolysis of Pickering emulsions, achieving a product density ≥2 g / cm³. 3 The goal of this invention is to eliminate the need for manual weaving. Using carbon fiber braided body as raw material, automated production can be achieved through a CNC system consisting of a high-temperature furnace, a vapor deposition furnace, a special impregnation fixture, a pyrolysis furnace, and a CNC milling machine. The traditional process in Comparative Example 2 requires more than three months to complete the production, while the process of this invention can be completed in just two months.
[0058] All other unspecified parts belong to the prior art.
Claims
1. A method for preparing a high-density C / SiC ceramic composite material, characterized in that: Includes the following steps: 1) Preform preparation: The carbon fiber braid is degummed and pyrolytic carbon is deposited to obtain a preform with pyrolytic carbon deposited on it; 2) A precursor solution was prepared using polycarbosilane as a precursor. The preform was subjected to multiple impregnation and pyrolysis treatments using the PIP process to obtain a density ≥1.75 g / cm³. 3 The blank; 3) A Pickering emulsion was prepared using silicon carbide as a raw material. This Pickering emulsion was then used to replace the precursor solution in multiple impregnation and pyrolysis treatments of the billet to obtain a density ≥2.0 g / cm³. 3 The billet is then subjected to a final impregnation pyrolysis treatment using the precursor solution. 4) The blank after impregnation and pyrolysis is machined and then heat-treated to obtain C / SiC ceramic composite material products.
2. The preparation method according to claim 1, characterized in that: The carbon fiber braid has an irregular structure.
3. The preparation method according to claim 1, characterized in that: In step 1), the degumming process includes: immersing the carbon fiber braid in a high-temperature furnace for three-stage heating; the first stage heating: heating from 400-800 min to 800-1000℃, holding for 100±30 min; the second stage heating: heating from 400-600 min to 1600-1800℃, holding for 100±30 min; the third stage heating: heating from 100-200 min to 1900-2500℃, holding for 240±30 min; during the first stage heating, argon gas is introduced during the holding period, with a flow rate of 1-3 L / min, maintaining the furnace pressure at 4-8 KPa until the three-stage heating is completed; after the heating is completed, the product is cooled to below 50℃ in the furnace and then removed.
4. The preparation method according to claim 1, characterized in that: In step 1), the pyrolysis carbon deposition process includes: transferring the degummed carbon fiber braid into a vapor deposition furnace, heating it to 700-1000℃ for 720-1440 min, and holding it at that temperature for 4320-5760 min; during the holding period, a mixture of methane and argon with a volume ratio of 3.5-4.5:1 is introduced, with a gas flow rate of 1-3 L / min, while simultaneously evacuating the furnace to a negative pressure and maintaining the negative pressure at 500-900 kPa until the heating is completed; after the heating is completed, the furnace is cooled to below 50℃, and the product is removed.
5. The preparation method according to claim 1, characterized in that: In step 2), the precursor solution comprises solid polycarbosilane and xylene in a mass ratio of 1:0.7~1.
5.
6. The preparation method according to claim 1, characterized in that: In steps 2) and 3), the impregnation pyrolysis process includes the following steps: Impregnation: The preform or blank is placed into an impregnation fixture containing a precursor solution, or the blank is placed into an impregnation fixture containing a Pickering emulsion, requiring all surfaces to be submerged, and the impregnation time is 12~36h; Curing: Take out the preform or blank after soaking, shape it with a shaping fixture, and cure it at a constant temperature of 40~60℃ for 12~36h to obtain a blank with the shaping fixture. Pyrolysis: The billet carrying the shaping fixture is transferred to the pyrolysis furnace. First, the furnace is evacuated to below 10 Pa, and nitrogen is introduced to replace the air in the furnace three times. Then, the furnace is evacuated again to 9~11 Pa. Next, two-stage heat preservation is carried out. The first stage: the temperature is raised to 800~1000℃ in 400~800 min and held for 100±20 min. The second stage: the temperature is raised to 1000~1500℃ in 400~600 min and held for 150±10 min. After the heat preservation is completed, the billet is cooled to below 50℃ in the furnace, the vacuum is released, the billet is taken out and the shaping fixture is removed.
7. The preparation method according to claim 1, characterized in that: In step 3), the Pickering emulsion comprises silicon carbide, xylene, and emulsifier in a mass ratio of 3:1.0~1.8:0.
05.
8. The preparation method according to claim 7, characterized in that: The emulsifier is silicon dioxide or modified silicon dioxide emulsifier; the silicon carbide is waste silicon carbide powder generated during the pyrolysis process.
9. The preparation method according to any one of claims 1 to 8, characterized in that: In step 4), the heat treatment temperature is 1000±50℃; the heat treatment process includes: transferring the machined billet to a pyrolysis furnace, firstly requiring the furnace to be evacuated to below 10Pa, then filling the furnace with nitrogen to replace the air three times, and then evacuating it again to 9~11Pa; starting the CNC panel to set the heating program, heating to 1000±50℃ in 400~800min, and holding for 100±20min; after the holding is completed, cooling it to below 50℃ with the furnace, removing the vacuum, and taking out the product.
10. A high-density C / SiC ceramic composite material product, characterized in that: The high-density C / SiC ceramic composite material is obtained by the preparation method according to any one of claims 1 to 9; the tensile strength of the product is ≥330 MPa, and the impact toughness is ≥40 KJ / (m). 2 (), bulk density ≥2g / cm³ 3 .